2004
DOI: 10.1167/iovs.03-1118
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Development, Limbal Stem Cell Function, and Corneal Epithelial Cell Migration in thePax6+/−Mouse

Abstract: The correct Pax6 dosage is necessary for normal clonal growth during corneal development, normal limbal stem cell activity, and correct corneal epithelial cell migration. Disruption of normal cell movement in heterozygotes may be the consequence of failure of nonautonomous guidance cues. Degeneration of the corneal surface in aniridia-related keratopathy relates to both a deficiency within the limbal stem cell niche and nonautonomous diversion of corneal epithelial cell migration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
130
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 139 publications
(146 citation statements)
references
References 34 publications
15
130
0
1
Order By: Relevance
“…The defective healing is observed both in mice models and clinically, and is related to abnormalities in the cell surface glycoconjugate and deficient and delayed extracellular matrix metabolism. 1,7,10,20,22,23 The volume of oxidized proteins increases with age in normal corneas but is more extensive in Pax6 +/-. Corneal epithelia, both superficial and basal cells in Pax6 +/-mice, have demonstrated more severe oxidative modifications.…”
Section: B Oxidative Stress Wound Healing and Corneal Transparencymentioning
confidence: 99%
See 3 more Smart Citations
“…The defective healing is observed both in mice models and clinically, and is related to abnormalities in the cell surface glycoconjugate and deficient and delayed extracellular matrix metabolism. 1,7,10,20,22,23 The volume of oxidized proteins increases with age in normal corneas but is more extensive in Pax6 +/-. Corneal epithelia, both superficial and basal cells in Pax6 +/-mice, have demonstrated more severe oxidative modifications.…”
Section: B Oxidative Stress Wound Healing and Corneal Transparencymentioning
confidence: 99%
“…8,10 In experiments with Pax6 +/-mice, several insights have been gained into impaired corneal wound healing. 16,20 One important finding was that increased stromal apoptosis occurred after wounding, and it has been suggested that apoptosis, as well as deficient and delayed extracellular matrix metabolism, aggravated the corneal changes. 16 A summary of the corneal wound healing and stromal response in AAK is given in Table 1.…”
Section: B Oxidative Stress Wound Healing and Corneal Transparencymentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, a coordinated centripetal movement of epithelial cells and nerves has been postulated in several studies. 38,39 The present study provides the first evidence in human corneas of an exact correspondence of epithelial cell and subbasal nerve patterns of movement, however, as noted in a recent study, 34 the mechanisms orchestrating this motion still remain unclear.…”
Section: Discussionmentioning
confidence: 52%